Advancements on the molecular design of nanoantibiotics: current level of development and future challenges. Issue 4 (25th July 2017) - Jijie, Roxana; Barras, Alexandre; Teodorescu, Florina; Boukherroub, Rabah; Szunerits, Sabine
Abstract : Numerous antimicrobial drugs have been developed and commercialized to kill and inhibit the growth of pathogenic microbes. Abstract : Numerous antimicrobial drugs have been developed and commercialized to kill and inhibit the growth of pathogenic microbes. The therapeutic efficiency of these drugs has however become often inadequate for the treatment of microbial infections, the reasons being multiple. Oral administration results often in only partial absorption and up to 50% of the active compound can be excreted in the urine. Furthermore, antibiotic therapy is also frequently accompanied by gastrointestinal complications, including vomiting, nausea and diarrhea. From a therapeutic point of view, the low solubility of antibiotics in lipid membranes presents a limitation for rapid and efficient treatment of infections. The preferred route for the delivery of antimicrobial drugs is the oral one; oral formulations capable of extending the duration of drug delivery and minimizing side effects have received much attention. The combination of antimicrobial agents with nanomaterials has been seen as a particularly promising strategy to overcome these limitations. Particulate formulations have proven their efficiency in achieving better pharmacokinetic profiles and improving the bio availability of several antibiotics. Antibiotic modified particles have shown their capability to protect some of the antimicrobial drugs from stomach acid and first-pass metabolisms in the gastrointestinal tract. Likewise, particle formulations can increase the circulation times of a drug and the local concentration gradient across absorptive cells. The present review describes the current status of different types of antibiotic loaded nano-systems. Key principles such as antibiotic loading, the release mechanism and the mode of action involved in pathogen killing or inhibition will be discussed in more detail. It is hoped that the general knowledge obtained here will help in the generation of advanced nanomaterials loaded with antimicrobials agents.